Management of Amavata (Rheumatoid arthritis) with herbo-mineral formulation -A clinical study - G, Venkateshwarlu; K, Giri S; S, Jonah; ORR, Sharma; SK, Sharma (International Journal of Ayurvedic Medicine, 2011)
Rheumatoid Arthritis (R.A) is a chronic, progressive and disabling auto-immune disease that causes chronic inflammation of the joints. It makes life miserable and crippling due to unknown cause, claiming the maximum loss of human working capacity. The polyarticular joint disease has been described in Ayurveda has high resemblance with Rheumatoid arthritis in modern medicine. The disease draws attention for the consideration of research firstly due to the gravity of the problem and secondly due to lack of adverse free modern drugs for the treatment of R.A. Hence the present study has been taken up to see the efficacy of a combination of herbomineral drugs i.e Sunthi, Guggulu and Godanthi bhasma (1:2:1 ratio) on 71 cases of Amavata (R.A). The study observations showed that the overall treatment response among the cases studied, 10 (15%) cases showed good response, 20 (30%) cases showed fair response, 33 (49%) cases showed mild response and 4 (06%) patients did not show any response and rest 4 cases were dropouts. There was a significant improvement in loss of appetite, anorexia, fever in amavata patients after treatment. Statistical analysis of the mean difference before and after treatment in relief on all the above symptoms except in sub cutaneous nodules and erythrocyte sedimentation rate (ESR), were found highly significant (P<0.0001). It was also observed a definite improvement and subjectively maximum patients had a feeling of well-being. No side effects were reported during and after the treatment.